2011
DOI: 10.1016/j.aap.2010.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of traffic accident injury severity on Spanish rural highways using Bayesian networks

Abstract: Several different factors contribute to injury severity in traffic accidents, such as driver characteristics, highway characteristics, vehicle characteristics, accidents characteristics, and atmospheric factors. This paper shows the possibility of using Bayesian Networks (BNs) to classify traffic accidents according to their injury severity. BNs are capable of making predictions without the need for pre assumptions and are used to make graphic representations of complex systems with interrelated components. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(110 citation statements)
references
References 20 publications
7
99
0
4
Order By: Relevance
“…This results are coherent with previous studies which have highlighted some of this variables as key variables in KSI accidents (Abel-Aty 2003;Al-Ghamdi, 2002;de Oña et al, 2011;Gray et al, 2008;Helai et al, 2008;Kashani and Mohyamany, 2011;Kockelman and Kweon, 2002;Pande and Abel-Aty, 2009;Montella et al, 2011).…”
Section: Severity Injury Analysissupporting
confidence: 92%
See 3 more Smart Citations
“…This results are coherent with previous studies which have highlighted some of this variables as key variables in KSI accidents (Abel-Aty 2003;Al-Ghamdi, 2002;de Oña et al, 2011;Gray et al, 2008;Helai et al, 2008;Kashani and Mohyamany, 2011;Kockelman and Kweon, 2002;Pande and Abel-Aty, 2009;Montella et al, 2011).…”
Section: Severity Injury Analysissupporting
confidence: 92%
“…The values of accuracy range from 64.0% in C1 to 55.1% in C4. These values are within the same range found in previous studies (Abdelwahab and Abdel-Aty, 2001;De Oña et al, 2011;Mujalli and De Oña, 2011) that used classification techniques for similar objectives. Table 4 shows that only C1 (64.0%) achieved a statistically significant improvement of accuracy as compared with results obtained for the EDB (59.5%).…”
Section: Severity Injury Analysissupporting
confidence: 88%
See 2 more Smart Citations
“…The factors associated with RTA's in the country are comparable to what one would expect in most countries, although a further breakdown of factors under 'other' categories is necessary since that particular category has over half the number of accidents. Other factors identified to contribute to traffic safety include the 4 E's: Engineering, Enforcement, Education and Emergency [11],while human error, vehicle and road network or infrastructure is also a factor in traffic safety reduction [12]. A recent study in the UAE [13] identified driving behaviour, awareness, education and training, infrastructure, vehicle and law enforcement as some of the main factors contributing to traffic safety in the country.…”
Section: Road Traffic Accidentsmentioning
confidence: 99%